Accreditation Surveyor and Patient Safety: Learning from World Patient Safety Day 2023 (Literature Review) - Ahyar Wahyudi; Friedrich Max Rumintjap; Hisnindarsyah; Nurhikmah; Listyo Yuwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article serves as a commemoration for World Patient Safety Day (WPSD) 2023, observed every 17th of September. Unlike previous years, this year’s theme is